Relationship Angle Take-Off the Vertical and Horizontal Velocity Effective and Accomplish the Long Jump for Women - Mutasher, Shatha Ali; Shammari, Ayad Abd Rahman al (International Journal of Psychosocial Rehabilitation, 2020)
Of the most important duties of Athletic Training Specialist To achieve a complete athlete requires knowledge of a lot of factors, mechanical and influencing it is due not achieving to, the neglect of some of the factors and this is the achievement of achievement of the most difficult issues facing, the sports training and those in his field. "Entered contests the long jump in the representation of the Olympic and since Year (1896) for men, since the first modern Olympics in Greece, either for the women entered the contest ,the long jump starting cycle year (1928) and follower of the achievements of international sports see if the sport in the development of a permanent and continuous it has won the effectiveness of the long jump attention to these experiences that helped us find the most important factors that must be taken care of and focus on to improve the level of achievement better. motor analysis is used in determining the level of performance movements and mathematical skills when players accurately, and in which you can extract the values of variables kinematical and compared with variables kinematical model to know the strengths and weaknesses of the performance of the players and contribute to modify this performance for the better. Hence the problem of searching through my work in academic research have noted the low level of achievement to the players the long jump even at the global level because of absence of the link between these variables under study during the performance, which formed the first omission of some of the coaches for drills associated with the physical side secondly the lack of interest in the analysis motor for the players I thought I should be my study compared to some of the variables kinematical for completion of the World for Men and Women Championship and He worsened at the 2011 in Birlen to be to serve as a model a good model of dynamic behavior of both sexes, and know the strengths and weaknesses they have.